The Taxation of Financial Capital under Asymmetric Information and the Tax-Competition Paradox - Wolfgang Eggert; Martin Kolmar (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
This paper examines information sharing between governments in an optimaltaxation framework. We present a taxonomy of alternative systems of international capital-income taxation and characterize the choice of tax rates and information exchange. The model reproduces the conclusion of the previous literature that integration of international capital markets may lead to the under-provision of publicly provided goods. However, different to the existing literature under-provision occurs because of inefficiently coordinated expectations. We show that there exists a second equilibrium with an efficient level of public-good provision and complete and voluntary information exchange between national tax authorities.
Keywords: H21; F42; F20; 330; tax competition; information exchange; Kapitalertrag; Internationaler Finanzmarkt; Informationsverhalten; Steuerwettbewerb; Öffentliches Gut; Theorie; information sharing